(untitled) (Research, Society and Development, 2022)
We will discuss here the use of distancing and social isolation in certain situations not related to the corona virus disease 2019 pandemic (COVID-19), as well as the articulation of these measures in current times, with the objective of presenting systematic mapping data of scientific disclosures that deal with isolation and social distancing in the pandemic of the new coronavirus and in other situations (home and hospital). The research has a quantitative-qualitative approach, with material collection in the Scientific Electronic Library Online (SciELO) and Web of Science databases, using iramuteq software as an instrument for analysis. The 18 selected articles showed the delimitation of social isolation in the theme, following different aspects, methods and techniques of study. Hospital situations involving children, adolescents and their companions, in addition to studies on isolation among former psychiatric patients in today’s society. The analyses presented in the cloud of words and similitude indicate that isolation and/or social distancing are linked to mental and physical health, the support network and socioeconomic vulnerability, in view of the inequalities of the country.